Density Functional Calculations on the Mechanical Properties of Nitrogen or Oxygen Doped Crystalline Ge2Sb2Te5 - Kim, Sae-Jin; Lee, Seung-Cheol; Choi, Jung-Hae (AMER SCIENTIFIC PUBLISHERS, 2012)
The mechanical properties of pure and doped crystalline Ge2Sb2Te5 were investigated by using density functional calculations. Nitrogen or oxygen was added at either the interstitial or substitutional sites of cubic Ge2Sb2Te5. The lattice parameter, elastic stiffness and related moduli were investigated from the viewpoint of the doping concentration, dopant species, dopant states and film direction. The effect of the doping concentration was more dominant than those of the dopant species and their states on the non-directionality properties, such as the bulk modulus and lattice parameter. It turned out that Ge2Sb2Te5 became slightly more rigid as the doping concentration of nitrogen or oxygen increased. On the other hand, the effect of the film direction on the directional properties, such as the biaxial modulus of the Ge2Sb2Te5 film, was found to be more predominant than that of doping. The biaxial modulus of the (001) oriented film was calculated to be much higher than those of the other films, indicating that the (001) film is the most vulnerable to thermal stress.
Keywords: TOTAL-ENERGY CALCULATIONS; THIN-FILMS; PHASE; MICROSTRUCTURE; BEHAVIOR